Advances and prospects of drug clinical research in colorectal cancer in 2022 - Dan Su; Chao Liu; Jie Cui; Jiebing Tang; Yuli Ruan; Yanqiao Zhang (Cancer Innovation, 2023)
Abstract Colorectal cancer (CRC) is the third most common cancer and the second leading cause of cancer death worldwide. Clinical research results have provided more treatment opportunities for CRC patients, showing that an optimal combination of existing drugs and new drugs is needed to mitigate the burden of this disease. In this review, we have summarized recent advances in drug clinical research for CRC in 2022, including chemotherapy, targeted therapy, and immunotherapy, to find opportunities for substantial improvements in drug discovery and clinical development methods.